Toxoplasmosis Prevalence in Sheep in Daerah Istimewa Yogyakarta - Nurcahyo, W; Prastowo, J; Sahara, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. A research on toxoplasmosis prevalence in sheep was conducted in Daerah Istimewa Yogyakarta. The objective of the research was to understand the prevalence level of toxoplasmosis in sheep using skin test method by taking the membrane protein of tachyzoit produced in vivo. The research was initiated by producing the tachyzoit membrane protein at the testing animals, later the obtained protein was prepared and used in the skin test method. At the end of the research agglutination test was conducted to confirm the diagnosis using card agglutination test. An optimal dosage of tachyzoit membrane protein used in sheep as the basic material of the skin test was 1.5 mg/ml/head. Result showed the reaction of skin was thickening and the duration after being injected intradermally varied from 12 to 30 minutes in various sizes from 8 to 19 millimetres. The skin test method showed that the prevalence level of toxoplasmosis in Yogyakarta was more than 70%.Key Words: toxoplasmosis, prevalence, skin test